2016
DOI: 10.3389/fpls.2015.01246
|View full text |Cite
|
Sign up to set email alerts
|

A De novo Transcriptomic Approach to Identify Flavonoids and Anthocyanins “Switch-Off” in Olive (Olea europaea L.) Drupes at Different Stages of Maturation

Abstract: Highlights A de novo transcriptome reconstruction of olive drupes was performed in two genotypesGene expression was monitored during drupe development in two olive cultivarsTranscripts involved in flavonoid and anthocyanin pathways were analyzed in Cassanese and Leucocarpa cultivarsBoth cultivar and developmental stage impact gene expression in Olea europaea fruits.During ripening, the fruits of the olive tree (Olea europaea L.) undergo a progressive chromatic change characterized by the formation of a red-bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 82 publications
(105 reference statements)
2
40
0
Order By: Relevance
“…During fruit formation and ripening in many plants, anthocyanin synthesis is enhanced by the co-regulation of a suite of TFs. Anthocyanins are considered as effective markers for monitoring ripening stages and the organoleptic quality of fruits [25]. Fang et al [8] demonstrated that the color of 'Furongli' plum (Prunus salicina) changed from green to red during ripening, which was associated with an evident increase in the anthocyanin content, being 53.85-fold higher at 135 days after flowering (DAF) in comparison to that at 105 DAF.…”
Section: Introductionmentioning
confidence: 99%
“…During fruit formation and ripening in many plants, anthocyanin synthesis is enhanced by the co-regulation of a suite of TFs. Anthocyanins are considered as effective markers for monitoring ripening stages and the organoleptic quality of fruits [25]. Fang et al [8] demonstrated that the color of 'Furongli' plum (Prunus salicina) changed from green to red during ripening, which was associated with an evident increase in the anthocyanin content, being 53.85-fold higher at 135 days after flowering (DAF) in comparison to that at 105 DAF.…”
Section: Introductionmentioning
confidence: 99%
“…Specially, it has been widely applied to investigate molecular mechanisms of flavonoids accumulation in plant species such as Dioscorea alata 16, Prunus avium 17, Olea europaea 18 and Gentiana straminea 19. Here, we present the transcriptome analysis of D. cambodiana using RNA-Seq complemented with HPLC flavonoid profiling to identify potential candidate genes involved in flavonoids accumulation.…”
mentioning
confidence: 99%
“…In order to obtain a general overview of the transcripts and metabolic pathways during pollen tube growth and to avoid cross contamination from nonhomogeneous tissue separation, sample pooling strategy was used here [ 11 , 12 ]. Pooling reduces variability by minimising individual variation and represents an alternative approach to biological replicates in experiments where interest does not focus on the individual but rather on characteristics of the population (e.g., common changes in expression patterns) [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each sequence set was filtered with these criteria: first, the read containing the sequencing adaptor was removed; second, the reads with unknown nucleotides comprising more than 5% were removed; and third, low-quality reads with ambiguous sequence “N” were trimmed and discarded. Subsequently, without a reference genome a de novo assembly of the clean reads into transcripts was performed using Trinity, a novel method for the efficient and robust de novo reconstruction of transcriptomes from RNA-Seq data [ 11 , 16 23 ].…”
Section: Methodsmentioning
confidence: 99%